PENGGUNAAN MEDIA GAMBAR DALAM PEMBELAJARAN MEMBACA DI KELAS 1 SDN 003 PULAU JAMBU KECAMATAN CERENTI - Apriyanti Apriyanti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
Reading learning plays an important role in primary school especially in grade 1. The students 'intelligence inprimary school is seen from students' reading ability because if students can not read other lessons will bedisturbed. Classroom action research is an improvement of the learning process to solve the problems thatteachers get in class. The data obtained after the research on the activity of the first cycle I teacher meeting withthe percentage of 50%, the second meeting with the percentage of 62.5%, in cycle II at the third meetingpercentage of 77.5%, and at the fourth meeting percentage of 97, 5%. Student observation data in this researchobtained the percentage of the first cycle of the first meeting of 52.5%, the second meeting of 62.5%, the thirdcycle of the third meeting of 75%, and the 4th meeting obtained by the percentage of 95% increased. The data ofreading skill in class 1 SDN 003 Pulau Jambu Kecamatan Cerenti on the initial data obtained an average of65.84, in the daily test I obtained the average class of 78.03, and in the daily test II obtained an average of 87.7this proves that the use of image media in effective reading learning is used.